Managing state budget available cash resources: Case study of Poland - Wojciech Misiąg; Jan Misiąg (Financial Internet Quarterly, 2025)
The aim of the paper is to review how free funds (available cash resources) are managed in the Polish state budget, to review the solutions used at the national and local levels in other countries and assess the quality of management in Polish conditions. Analysis of the budget available cash resources covered the last twelve years and included both periods of economic growth as well as crisis years. Methodology of the research included financial analysis of state budget revenues, expenditure, debt income and debt repayment expenses, as well as public debt statistics and ear-marked funds data. The results obtained during the study provide for the formulation of a negative opinion regarding the management of available funds in the state budget. Based on the research results, the authors prepared a number of recommendations, the implementation of which will increase the effectiveness of public funds management.
Keywords: E52; E58; E60; 330; Cash Resources; Countercyclical Actions; Public Finance; State Budget